Constraints experienced by beginning secondary science teachers in implementing scientific inquiry lessons - ROEHRIG, Gillian H; LUFT, Julie A (International journal of science education, 2004)
'Science as inquiry' is a key content standard in the National Science Education Standards to be enacted by US science teachers. This paper is the result of a study that was conducted in order to understand factors that impacted the inquiry-based instruction of 14 beginning secondary science teachers. These teachers were part of a collaborative university/school district induction program designed to facilitate inquiry-based instruction. For a period of 1 year, the teachers were followed in an attempt to understand their teaching beliefs, instructional practices, knowledge of the nature of science and scientific inquiry, and their experiences with inquiry instruction in the classroom. Case and cross-case comparisons revealed five main constraints that impacted their enactment of inquiry-based instruction: an understanding of the nature of science and scientific inquiry, content knowledge, pedagogical content knowledge, teaching beliefs, and concerns about management and students. This study reinforces the need for standards-based induction programs that offer various forms of support to assist beginning science teachers. Reprinted by permission of Taylor & Francis Ltd.